Multispectral Remote Sensing Satellite Data for Mineral and Hydrocarbon Exploration: Big Data Processing and Deep Fusion Learning Techniques (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint exists to solve high complexity issues in remote sensing data processing, geochemical data analysis, geophysical data analysis and appropriate applications of GIS techniques for data fusion designed for mineral and hydrocarbon exploration. This reprint contains updated and informative knowledge of remote sensing imagery, geochemistry, geophysics and geospatial techniques that can assist in delineating the signatures and patterns linked to deep-seated, covered, blind, or buried mineral deposits and onshore oil slick detection, offshore oil spill monitoring and hydrocarbon exploration. It includes several color figures for remotely-sensed recognition of mineralization-related footprints. Additionally, this reprint comprehends several interactive flowcharts for describing the procedures explained therein.